2020
DOI: 10.1177/0896860820972598
|View full text |Cite
|
Sign up to set email alerts
|

Persistent colonization of exit site is associated with modality failure in peritoneal dialysis

Abstract: Exit-site infections (ESIs) increase the risk of developing peritoneal dialysis (PD) peritonitis and PD technique failure. There are no clear guidelines on how to monitor exit site (ES) after ESI with Staphylococcus aureus or Pseudomonas. We report on a 1-year observational study of 23 patients who developed an ESI with one of these serious pathogens. After completing initial antibiotic treatment, swabs were taken every month for 3 months. Primary treatment cure occurred in 19/23 (83%). Colonization of ES afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…The ISPD does not formally recommend repeating an exit-site culture 1-2 weeks post antibiotic completion, though small studies have shown that subsequent colonization is associated with a significantly increased risk of catheter loss and repeat ESI [2,68]. Given repeat ESI has an estimated 65% risk of subsequent peritonitis and 50% risk of transfer to HD, there may be utility in repeating and treating a positive exit site culture within 2 weeks of antibiotic completion [10].…”
Section: Management Of Refractory Esimentioning
confidence: 99%
“…The ISPD does not formally recommend repeating an exit-site culture 1-2 weeks post antibiotic completion, though small studies have shown that subsequent colonization is associated with a significantly increased risk of catheter loss and repeat ESI [2,68]. Given repeat ESI has an estimated 65% risk of subsequent peritonitis and 50% risk of transfer to HD, there may be utility in repeating and treating a positive exit site culture within 2 weeks of antibiotic completion [10].…”
Section: Management Of Refractory Esimentioning
confidence: 99%
“…However, monitoring culture after primary cure of the exit site infection has been shown to detect persistent colonisation which was associated with higher risks of peritonitis 107 and transfer to haemodialysis. 107,108…”
Section: Monitoring and Duration Of Therapymentioning
confidence: 99%
“…10 In a recently published study on the issue of persistent colonization of PD catheter exit sites, the authors noted that patients who were infected with recurrent Pseudomonas (at the exit site) were reminded to clean their showerhead with bleach monthly. 11 Similarly, a paper on the care of an infected PD catheter exit site has recommended that during a home visit a check on cleaning of the showerhead should be performed. 12 Equally, the UK Kidney Association recommends monthly descaling of showerheads for patients on PD.…”
Section: Cleaning Of the Showerheadmentioning
confidence: 99%
“…The definitions for repeat, recurrent or chronic are not discussed. We have noticed that recently published studies and guidelines do use differing definitions for repeat 11,16 and for chronic exit-site infections. 6,17 In a review of the epidemiology of PD catheter exit-site infections, the authors also observed that there are no standard definitions for repeat, relapsing or recurring exit-site infections.…”
Section: Exit-site Infection Classification and Terminologymentioning
confidence: 99%